Investigation of Job Satisfaction among Female Teachers of Secondary School of Uttar Pradesh: Exploring Factors Influencing Job Satisfaction among Female Secondary School Teachers in Uttar Pradesh (Journal of Advances and Scholarly Researches in Allied Education, 2016)
This investigation uncovers that optional teachers in Uttar pradesh, Sabah were for the most part happy with their employment; there is a huge connection between work fulfillment and sexual orientation, whereby the male instructors were for the most part more fulfilled than female educators. The graduate instructors were more fulfilled than non-graduate educators. The higher positioning educators were more fulfilled than the customary instructors while the more seasoned educators were more fulfilled than their more youthful partners. Be that as it may, there is no noteworthy connection between spots of starting point of educators with work fulfillment. In light of the bivariate connection tests, six work measurements of showing work are fundamentally identified with educators' employment fulfillment. Moreover, there were noteworthy distinctive between the six measurements by sex and administration classification of instructors. Just associates measurement is not essentially extraordinary among instructors' vocation arrange and their residency of administration. There was no noteworthy contrast between all the work measurements and educators' place of root. In light of the discoveries of the investigation a few proposals are sent.